Occurrence of indicator bacteria and pathogens in the waters of the noyyal river near its source and downstream in coimbatore district - P, Zion Meshach; G. Sargunar, Clara (Kongunadu Research Journal, 2020)
Water, the bloodstream of the biosphere, also acts as a sink, solvent and transport vehicle for domestic, agricultural and industrial waste, causing pollution. The Noyyal River, a tributary of the River Cauvery, was once the lifeline of Coimbatore, but is now being threatened by pollution from various sources. Assessments of microbiological water quality have focused on the presence of Fecal Indicator Bacteria, which indicate that a contamination pathway exists between a bacterial source and the water supply, serving as a route for pathogen entry. Water samples from seven sites (Kooduthurai, Madakkadu,Thombilipalayam, Alandurai, Mathampatti, Perur and Aathuppalam) along the Noyyal, were analyzed for various microbiological characteristics. The results indicated that the river was relatively unpolluted upstream near its sources, but is progressively polluted on moving further downstream towards Coimbatore city. Levels of Total Heterotrophic Bacteria, indicators such as Enterobacteriaceae, Total Coliforms, Fecal Coliforms (FC), Fecal Streptococci (FS), pathogens like Salmonella sp., Shigella sp., and Vibrio sp. were elevated at downstream sampling sites. Evaluation of the FC:FS ratio revealed that, the water was unfit for drinking at almost all the downstream sampling stations, and could have limited use for irrigation. The release of fecal microorganisms and pathogens from the sediments to the water column could be a major source of bacterial loading. Non-point sources were identified as the major contributors of contaminants. Regular monitoring of the river water and sediment, amelioration of point / non-point sources of pollution, and speedy implementation of remedial measures, may restore this stretch of the Noyyal River to its former pristine state.